SSSR Presidential Address Rain Dances in the Dry Season: Overcoming the Religious Congruence Fallacy. - Chaves, Mark (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2010)
Religious congruence refers to consistency among an individual's religious beliefs and attitudes, consistency between religious ideas and behavior, and religious ideas, identities, or schemas that are chronically salient and accessible to individuals across contexts and situations. Decades of anthropological, sociological, and psychological research establish that religious congruence is rare, but much thinking about religion presumes that it is common. The religious congruence fallacy occurs when interpretations or explanations unjustifiably presume religious congruence.